2016
DOI: 10.4070/kcj.2016.46.6.768
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Lymphocyte Ratio as a Predictor of Left Ventricular Apical Thrombus in Patients with Myocardial Infarction

Abstract: Background and ObjectivesIn this study, we examined the role of inflammatory parameters in an apical mural thrombus with a reduced ejection fraction due to large anterior myocardial infarction (MI).Subjects and MethodsA total of 103 patients who had suffered from heart failure, 45 of whom had left ventricular apical thrombus (AT) after a large anterior MI, were enrolled in the study. A detailed clinical history was taken of each participant, biochemical inflammatory markers, which were obtained during admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“… 31 Furthermore, previous studies have shown both neutrophilia and lymphocytopenia to be independently and strongly associated with an increased risk of complications and mortality post-AMI. 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Similar to our study, Horne et al investigated patients with coronary artery disease (CAD) (without MI) to check whether inflammatory markers can help to identify the risk of death/MI. The study followed up over 3000 patients on a long-term basis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“… 31 Furthermore, previous studies have shown both neutrophilia and lymphocytopenia to be independently and strongly associated with an increased risk of complications and mortality post-AMI. 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Similar to our study, Horne et al investigated patients with coronary artery disease (CAD) (without MI) to check whether inflammatory markers can help to identify the risk of death/MI. The study followed up over 3000 patients on a long-term basis.…”
Section: Discussionsupporting
confidence: 69%
“…Recent accumulating evidence points that high NLR to be independently and strongly associated with increased risk of complications and mortality post-acute MI. 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Here, our aim is to evaluate the level of NLR that is associated with myocardial dysfunction (EF and FS from echocardiography) or damage (CK-mB) in 715 myocardial infarction patients. NLR is readily available, so it may be used as a cost-effective adverse predictor.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also observed that high NLR levels are often associated with complex coronary arteries in patients [ 39 , 40 ]. Left ventricular apical thrombus and remodeling were also found to be related to high NLR [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil lymphocyte ratio (NLR) is a whole blood count test that is obtained by dividing the total number of neutrophils by the total lymphocyte count, and it has been reported that it can be an easily calculated parameter in indicating systemic inflammation (11,12). It is known that NLR is increased in many diseases such as malignancies, diabetes and myocardial infarction (13)(14)(15). Although BP is a disease in which inflammation takes part in its etiology, to our knowledge, there is no previous study in the literature investigating the relationship of NLR with this disease.…”
Section: Introductionmentioning
confidence: 99%